Lama Penyimpanan Ekstrak Buah Bitung (Barringtonia asiatica L. ) terhadap Mortalitas Hama Crocidolomia pavonana F. pada Tanaman Kubis (JURNAL ENFIT : Entomologi dan Fitopatologi, 2019)
One way to reduce various problems due to the use of synthetic insecticides is to develop effective and environmentally friendly means of control by using insecticides derived from plants (plant-based insecticides). The aim of this study was to study the storage duration of B. asiatica beetroot (seed) extracts stored at 100C (refrigerator) against mortality of C. paconana pests. The study was conducted at the Center for the Protection and Testing of Food Crops and Horticulture in North Sulawesi Province, for 6 (six) months from November 2018 to May 2019. Using a Completely Randomized Design (CRD) with 7 (Seven) treatment and 5 (Five) replications . The treatment is the storage time of bitung fruit (seed) extract (0 days, 6 days, 12 days, 18 days, 24 days, 30 days and 36 days). The results showed that the feeding activity and the motion activity of C. pavonana larvae after application with the extract of B. asiatica greatly decreased and eventually died. The results showed a relationship between the fast and long days of storage of B. asiatica extracts and mortality of C. pavonana larvae, the faster the application of B. asiatica extracts, the higher the mortality rate of test insects. B. asiatica extracts stored at 100C (refrigerator) for up to 36 days show mortality above 50%, this proves that the application of extracts stored at 100C (refrigerator) is effective in controlling C. pavonana larvae test insects.